Antiurolithic efficacy of a phenolic rich ethyl acetate fraction of the aerial parts of Aerva lanata (Linn) Juss. ex Schult. in ethylene glycol induced urolithic rats. (8th February 2021) - Mandal, Bitasta; Madan, Swati; Ahmad, Sayeed; Sharma, Arun K; Ansari, Mohd Hafizur Rehman
Abstract: Objectives: The study was carried out to evaluate the in vivo antiurolithic efficaciousness of an ethyl acetate fraction of Aerva lanata (EAFAL) derived from the hydromethanolic extract of its aerial parts (HMEAL). Methods: In vivo pharmacological potency of EAFAL was assessed by ethylene glycol (EG) induced urolithiasis model in male Wistar albino rats. Urine samples of the animals were analysed for physical parameters, stone promoters, inhibitors along with an evaluation of the biochemical parameters of serum and kidneys. Histopathological investigation of the kidneys was done. The fraction was further subjected to LC-MS and HPLC for its phytochemical evaluation. Key findings: EAFAL demonstrated a significant antiurolithic effect by a restoration of the balance between urinary promoters and inhibitors along with an amelioration of the urinary pH. The abnormally elevated levels of serum nitrogenous substances, calcium, albumin, globulin, total protein along with altered renal calcium, oxalate and uric acid were also alleviated significantly followed by an improvement of the histopathological aberrancies. Phytochemical analysis showed evidence of phenolic components and flavonoids. Conclusions: The current findings prove the beneficial role of phenolic and flavonoid rich EAFAL in ameliorating urolithiasis induced abnormalities of urine, serum and kidneys.